Fatal Craniocerebral Injuries in Two-Wheeler Road Traffic Accidents: A One Year Postmortem Study at a Tertiary Care Hospital in South India (Journal of Forensic Medicine & Toxicology, 2026)
Background: Road traffic accidents constitute a major and growing public health problem worldwide. While advances in medical science have significantly reduced mortality from communicable and non-communicable diseases, accidental injuries—particularly those related to motor vehicle use—have emerged as a leading cause of preventable death. Among road users, two-wheeler occupants are especially vulnerable, with head injuries accounting for the majority of fatal outcomes. Aim: To analyze the pattern and distribution of fatal craniocerebral injuries among victims of two-wheeler road traffic accidents. Materials and Methods: A cross-sectional descriptive autopsy-based study was conducted in the Department of Forensic Medicine and Toxicology, Karnataka Medical College & Research Institute (KMC-RI), Hubballi, over a period of one year. A total of 57 fatal cases of two-wheeler accidents in which head injury was certified as the cause of death were included. Detailed information was obtained from police records, hospital case sheets, relatives, scene photographs, and thorough postmortem examinations. Data were analyzed using descriptive statistics. Results: The majority of victims belonged to the 21–30-year age group, with a marked male predominance. Most fatal ities involved riders rather than pillion riders, and helmet non-use was observed in the majority of cases. The most common post-injury survival period among hospitalized victims ranged from one day to one week. Contusions were the predominant scalp injury, fissured fractures were the most frequent skull vault fractures, and combined subdural and subarachnoid hemorrhages constituted the most common intracranial findings. Countercoup injuries were observed more frequently than coup injuries.
Keywords: Craniocerebral injuries; Two-wheeler accidents; Intracranial hemorrhage; Autopsy; Road traffic fatalities